The balanced development of the summer and winter Olympics in China - Song, X.; Li, M. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction The Olympics Games, including both the summer and winter Games, characterizes the Olympic Movement. China regained its legal status in the International Olympic Committee in 1979. China`s real contact with the Olympic Games started with the Winter Olympic Games held in 1980. However, even with progresses over nearly 30 years, the two events demonstrate that there is a lack of balance between the summer and winter Olympic Games. This paper analyzes the main factors that affect the development of the summer and winter Olympic Games. The present analysis will enable information to be collected for future research on Olympic Sports with particular interest paid to the winter Olympics. Methods Methods used involved a literature review and statistical analysis. Results The literature review detailed the historical development of the summer and winter Olympic Games in China. This study analyzed the differences of the summer and winter Olympic Games, and presents some theoretical references for improved and balanced development of future Olympic Games. Discussion / Conclusions The main factors which affect the lack of balance between the development of the winter and summer Olympic Games include international influences, the number of events held at each (28 events in the summer Olympic Games, only 7 in the winter Olympic Games), cultural, historical and traditional factors, geographical factors, and differing social and economic benefits resulting from the summer and winter Olympic Games. Constructive suggestions for the balanced development of the summer and winter Olympic Games in China include the regulation of the development of sports, increasing the international influence of the winter events in China, public encouragement to participate in winter sports, and applying the knowledge gained from predominant events of the summer Olympics to develop the winter events.